Flexible Transparent Nanogenerators Utilizing Shape‐Modulated ZnO Nanorod Arrays on Graphene Electrodes. Issue 4 (16th February 2018) - Son, Myungwoo; Jang, Hanbyeol; Lee, Mi‐So; Yoon, Tae‐Ho; Lee, Byoung Hun; Lee, Woong; Ham, Moon‐Ho
Abstract: Flexible and transparent hybrid piezoelectric nanogenerators (PENGs) are prepared, based on vertical arrays of shape‐modulated ZnO nanorods (ZnO‐NRs) placed between two single‐layer graphene sheets. A simple transfer printing method using polydimethylsiloxane (PDMS) stamps in conjunction with polyethylene terephthalate (PET) enables the fabrication of flexible stacked structures of ZnO‐NRs/graphene/PDMS/PET, and the morphology of the ZnO‐NRs is controlled by metallic additives during their hydrothermal synthesis. The hybrid PENGs are transparent and generated electrical power upon bending; the power output performance is dependent on the nanorod morphology with a net volume power density of 0.0513 mW mm −3 for Cd‐doped ZnO‐NRs, which is comparable to that of today's energy storage devices. The variation in output power is ascribed to the differences in the deformation modes of ZnO‐NRs on bending because of the differences in their aspect ratios that are, in turn, controlled by the metallic additives; this suggests the possibility of customizing the power generation characteristics within a single material system. Abstract : Flexible and transparent hybrid piezoelectric nanogenerators based on vertically aligned, shape‐modulated ZnO nanorod (ZnO‐NR) array and graphene electrodes are prepared by a stamping transfer method on flexible substrates. Both the shape and concentration dependencies of the piezoelectric properties of the ZnO‐NRs are discussed, and the largest piezoelectric power generation is obtained for Cd‐doped ZnO‐NRs having a very low aspect ratio.